Тематика рекламных текстов в современном английском и французском языках - Мельник, Ю.А.; Норец, Т.М. (Культура народов Причерноморья, 2014)
В данной работе исследуются вербальные единицы разных уровней, функционирующие в
современных французских и английских рекламных журнальных текстах. В последнее время повысилась
роль в обществе социальной коммуникации, особым видом которой является реклама. Она несет в себе
определенную культуру, набор знаний, оказывает опосредованное влияние на формирование мнений,
поведение людей и общественное сознание. При условии определённой структуры, языка, «интонации»
текста, уместном использования языковых средств, рекламное послание будет пользоваться успехом у
читателей. У даній роботі досліджуються вербальні одиниці різних рівнів, що функціонують у сучасних
французьких і англійських рекламних журнальних текстах. Останнім часом підвищилася роль в
суспільстві соціальної комунікації, особливим видом якої є реклама. Вона несе в собі певну культуру,
набір знань, надає опосередкований вплив на формування думок, поведінку людей і суспільну свідомість.
За умови певної структури, мови, « інтонації » тексту, доречного використання мовних засобів,
рекламне послання буде користуватися успіхом у читачів. This paper examines different levels of verbal units functioning in modern French and English texts
of journal advertising. Nowadays, the role of social communication in the society is increasing, in particular the
usage of advertising. Advertising is a socio-economic phenomenon, which consists of many components. It has a
broad social context in different domains: economic, political, religious and moral. It carries a certain culture, a
set of knowledge; it has a great effect on the formation of opinions, behavior and social consciousness. From the
viewpoint of advertising communication can be defined as controlled impact implemented by means of mass
communication, which is carried out through the exchange of specially designed texts and visual materials.
Advertising should attract attention, have an impact on consumers' emotions and inform them. The text of
advertising (slogan) and the picture, which are printed on the paper or exist in audiovisual form, represent a
motivated, holistic, semantic and hierarchically organized symbolic formation. It is also a unit of communication
and cultural facility, fixed on media. Representing a particular social reality, advertising is a set of the most
frequently used patterns of behavior, activities, communication and interaction. Provided with certain structure,
language, "tone" of the text and the use of appropriate language means the advertising message will have a
success.